Caso de estudio para la caracterización de los personajes del Pase del Niño Rey de Reyes para la puesta en valor del patrimonio cultural de la ciudad de Riobamba - Arroba Guaraca, Kathi Juliana (2026)
The present research focuses on the characterization of Pass del Nino Rey de Reyes, as part of a strategy for valorizing the intangible heritage of the City of Riobamba. The objective is to investigate, realize and convey this heritage through the iconographic, iconological and morphological analysis of their personifications, production of artistic works and presentation to the people of Riobambe. The focus of the research is qualitative and so five key informants were interviewed, who shared with us their anecdotes of what they know and have lived as part of the traditional characters. This analysis also allowed us to identify the distinctive features and symbols that each character has, their evolution over the years, and their relevance to the city's cultural heritage. The results were significant works that were exhibited in an arts and cultural center in the city of Riobamba, thus creating an atmosphere of dialogue between viewers. The purpose was to preserve and keep alive this cultural tradition so that as time passed new generations would continue its practice and the city's heritage would be preserved intact.